Learning the English Language within Multilingual Context - Sevdimaliyeva, Sariyya; Afet, Hajiyeva (IJRDO- Journal of Educational Research, 2018)
The article explores the benefits of learning and knowing English in a multilingual context. Nowadays, knowing more than one language is a requirement for many people worldwide in order to compete with other professionals within the business environment. In today’s world, English, as a chief language of international business, is spoken as a second or third language in many countries around the world. In many multilingual countries, English is considered one of the main languages, which ease the process of communication and interaction among different individuals, people, and societies. So that English can be considered as a core factor in the creation and development of multilingualism within society. Research evidence suggests that having more than one language generates varied kinds of networks in the brain, which gives multilingual individuals advantages and benefits in some respects compared to other monolingual individuals. Thus, knowing the English language plays an important role not only in developing communication skills but also in achieving success in career life.